Companion encyclopedia of theology - Byrne, Peter, 1950-; Houlden, J. L. (James Leslie) (Routledge reference., 1995)
The Companion Encyclopedia of Theology provides a comprehensive guide to modern theological thought. An international team of theologians and practitioners of both the Christian and Jewish faiths investigate and consider aspects of theology in 48 self-contained articles. --From publisher's description.